Comprehensive Case Report: Bipolar Affective Disorder with a Current Manic Episode and Psychotic Symptoms in an Adolescent Male Triggered by Chronic Bullying in a Rural Area of Southwest Sumba - Ni Putu Intan Sri Maharani; I Gusti Ngurah Wisuda Manik (CV. Publikasi Indonesia, 2026)
Bipolar affective disorder (BAD) in adolescents is a chronic psychiatric condition with complex clinical manifestations and high risk of psychotic symptoms. Environmental factors, particularly bullying, have been identified as major stressors that can trigger disease onset through the kindling phenomenon. In remote areas such as Southwest Sumba, diagnostic challenges and limited treatment access are major obstacles to patient recovery. To report the clinical journey and successful management of an adolescent male with BAD manic episode with psychotic symptoms triggered by chronic bullying in a rural setting. Case report with data collection through in-depth family interviews, clinical mental status observation, and medical record review over a six-month period. Findings: Patient MPB (17 years) experienced systematic physical and verbal bullying during junior high school leading to school dropout. Psychotic symptoms manifested as visual hallucinations of a